Managing Civility in Public Comment Sessions at Town Council Meetings - Brett G. Johnson (Washington University Journal of Law and Policy, 2026)
Many (if not most) town councils in the United States grant members of the public the opportunity to speak before their elected representatives. Most of these councils have rules regulating these ‘public comment’ sessions. This Article first discusses the constitutionality of such ‘civility codes.’ Then, it analyzes these rules across 83 municipalities in six New England states, identifying several common trends among these codes that have significant implications for restrictions on the public’s First Amendment right to freedom of speech. Namely, this analysis finds problems with vague standards for ‘civility’ or ‘decorum’ that, when commingled with otherwise content-neutral restrictions on speech during public comment sessions, creates an environment where abuses of power by local officials all too keen to censor can grow unchecked. This Article provides solutions for how cities and towns can address this issue.
Keywords: #CivilityCodes; #PublicComment; #TownCouncilMeetings; #FreeSpeech; #FirstAmendmentViolation